A confined carbon dot-based self-calibrated fluorescence probe for visible and highly sensitive moisture readouts. (21st January 2022) - Ding, Zhong-Zheng; Zheng, Guang-Song; Lou, Qing; Han, Jiang-Fan; Wu, Meng-Yuan; Shen, Cheng-Long; Zang, Jin-Hao; Liu, Kai-Kai; Dong, Lin; Shan, Chong-Xin
Abstract: Excellent luminescent materials are essential for high-performance fluorescent nanosensors. Here, a new-type of self-calibrated humidity sensor is established through monitoring the fluorescent color change of carbon dots (CDs) confined in sodium hydroxide (CDs@NaOH). The CDs are prepared by a facile and rapid microwave-assisted heating method using citric acid, urea, and NaOH as precursors. The confinement effect from the NaOH reduces the nonradiative transition and suppresses the aggregation-induced quenching of the CDs in the solid. Compared with other sensors based on CD fluorescent visualization, the sensor has good linearity and a wide humidity-detection range from 6.9% to 95.4%. With the increased relative humidity, the fluorescence color of the sensor changes from green to blue. The proposed sensing mechanism is due to the breaking and reforming of hydrogen bonds and proton transfer occurring at the CD-NaOH matrix interfaces. These findings suggest a potential role for the spatial confinement effect and may provide an avenue for developing highly sensitive humidity readouts.